2019
DOI: 10.1080/10942912.2019.1646272
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profiles and antioxidant capacities of mulberry ( Morus atropurpurea Roxb.) juices from different cultivars

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Phenolic profiles and antioxidant capacities of mulberry (Morus atropurpurea Roxb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The addition of methoxyl moiety at the 5' position on the B ring (petunidin) can decrease radical scavenging activity 3-fold, compared to the one without (cyanidin) [25]. Additionally, glycosylation processes, including a number of sugar residues, types and positions of sugar, and types of glycosidic bond on anthocyanidins, vary the stability of anthocyanins, leading to different antioxidant capacities [25,29]. Interestingly, the increased number of sugar moieties at the C3 position on the C ring of anthocyanins ( Figure 1) can decrease antioxidant activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of methoxyl moiety at the 5' position on the B ring (petunidin) can decrease radical scavenging activity 3-fold, compared to the one without (cyanidin) [25]. Additionally, glycosylation processes, including a number of sugar residues, types and positions of sugar, and types of glycosidic bond on anthocyanidins, vary the stability of anthocyanins, leading to different antioxidant capacities [25,29]. Interestingly, the increased number of sugar moieties at the C3 position on the C ring of anthocyanins ( Figure 1) can decrease antioxidant activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…The genus Morus, belonging to the family Moraceae, comprises 24 Morus species and approximately 100 cultivars of known subspecies. Most species were discovered in Asia. , Among these species, Morus alba L. is native to Japan, China, and Korea and has been cultivated for centuries for the sake of its medicinal and economic value. In particular, Morus alba L. (white mulberry) has provided custom medicine in the Orient .…”
Section: Introductionmentioning
confidence: 99%
“…The compounds isolated from the aqueous extract of Mimela sp. viz., D-Pinitol obtained from carob tree are known to have antidiabetic, anticancer, antioxidant and anti-inflammatory activity (Azab, 2022), Benzoic acid are known to counteract pathogen related damage and yield loss in lettuce plants thereby acting as antimicrobial agent (Windisch et al, 2021), 17hydroxylinolenic acid are found to have anti-inflammatory activity in mammalian cells (Kolar et al, 2019), 2-Methylbenzaldehyde obtained from Cymbopogon martini essential oil has been reported to exhibit antioxidant, antibacterial and antifungal activities (Soorya et al, 2013), L-Onithine and Trans-zeatin are known to have immunological potential (Mika et al, 2014;Hallmark, 2020), 5,6,7,8-Tetrahydro-2,4-dimethylquinoline are known to have antitumor, antimicrobial, antiviral and immunoregulatory effects (Saurabhi et al, 2020), 2,4-Dihydroxy benzoic acid, 9,10, Dihydroxy-12-13-epoxyoctadecanoate and Citronelloglucoside are reported to have antioxidant, anticancer, antimicrobial, antidiabetic activity (Azab, 2022;Zhenjiang 2019;Ashwini, 2015;Santos, 2019) repectively. (R)-(+)-2 Pyrrolidone-5-carboxylic acid, 2,3-Dihydro-6-methyl-1-5-propanoyl-1Hpyrrolizine and 3,5-Dimethyl-2-propylpyrazine are known to have antimicrobial activity (Yang et al, 1997;Moreira et al, 2018;Cherniienko et al, 2022), 2,3-Dihydro-6-methyl-1-5-propanoyl- 1H-pyrrolizine are also known to have anti-inflammatory potentials besides Indoleacrylic acid (Wlodarska et al, 2017), O-Desmethylquinine are known to have antimalarial, antipyretic activity (Adnyana et al, 2013), 2 S-hydroxyoctadecanoic acid are known for antiallergic activity (Korinek, 2017), Gentisic acid for antidiabetic activity (Mechchate, 2021), Coiine reported to have antinociceptive effect (Arihan et al, 2009), Stovaine is used as local anesthesia (Wlodarska et al, 2017), Procaine is reported to have analgesic potential (Outland and Hanlon, 1940), Glutamylisoleucine in used as a potential biomarker of prostate cancer (Thacker, 2021) and Fabianine isolated from Aerva sanguinolenta (L).…”
Section: Resultsmentioning
confidence: 99%